Allogenic Amniotic Tissue for Treatment of Knee and Hip Osteoarthritis - Ashim Gupta (MDPI AG, 2022)
Osteoarthritis (OA) impacts millions of people and places a high burden on healthcare systems in the United States. Current treatment modalities have limitations and do not address underlying pathology. Lately, there has been an immense growth in the use of biologics, including perinatal allogenic tissues for orthopedic regenerative medicine applications. Amniotic tissue is an exciting new alternative for such applications. Despite several published studies that reported its use for treatment of ophthalmic conditions and complex wounds, there are limited clinical studies evaluating its safety and efficacy in treating patients suffering with knee or hip OA. In this manuscript, I focused on three prospective clinical studies which evaluated the safety and efficacy of amniotic tissue in patients suffering with moderate knee or hip OA. The results from these studies presented the scientific community with much needed, well-executed, and prospective clinical trials. Though these trials demonstrated that administration of amniotic tissue in knee or hip joint is safe and potentially effective, more multi-center, prospective, double-blinded, randomized controlled trials are warranted to further establish the efficacy of amniotic tissue to mitigate symptoms of knee and hip OA to ultimately justify its clinical use.